1999
DOI: 10.1142/s0192415x99000380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Uncariae Ramulus et Uncus on Endothelium in Spontaneously Hypertensive Rats

Abstract: The protective effect of the extract of Uncariae ramulus et Uncus (URE) against endothelium disorder due to hypertension was investigated. We administered low (150 mg/kg/day) and high (450 mg/kg/day) doses of URE orally to spontaneously hypertensive rats for 8 weeks. Endothelium dependent vasodilatation by acetylcholine increased significantly in the high URE group compared with the control group. Endothelium dependent vasocontraction by xanthine oxidase decreased significantly in the high URE group compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…It also is used to relieve headache, dizziness, and tremors resulting from hypertension (Goto et al, 1999). Several studies have described the potent anti-hypertensive and vasodilator functions of UR in animal models of hypertension (Goto et al, 1999(Goto et al, , 2000Shi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also is used to relieve headache, dizziness, and tremors resulting from hypertension (Goto et al, 1999). Several studies have described the potent anti-hypertensive and vasodilator functions of UR in animal models of hypertension (Goto et al, 1999(Goto et al, , 2000Shi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It also is used to relieve headache, dizziness, and tremors resulting from hypertension (Goto et al, 1999). Several studies have described the potent anti-hypertensive and vasodilator functions of UR in animal models of hypertension (Goto et al, 1999(Goto et al, , 2000Shi et al, 2003). Additionally, UR and its constituent, alkaloids have been reported to have a neuroprotective effect on glutamate-induced cell death (Itoh et al, 1999;Goto et al, 2000), Ca2+-blocking inhibitory activity (Suk et al, 2002), and anti-oxidative activity (Lin et al, 1995;Hou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, anti-contractive effects were considered to be active in vivo. These results were supported by our last study in which URE appeared to protect the function of endothelial cells in spontaneously hypertensive rat (Goto et al, 1999). As a next step, it will be necessary to administer URE to hypertensive patients and to study the effects on blood pressure and the complications of hypertension.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, we reported that the extract of Uncariae ramulus et Uncus has a protective effect for the endothelium against the influence of hypertension in spontaneously hypertensive rat. The mechanism suggested that Uncariae ramulus et Uncus had a vasodilator effect and an anti-oxidant effect on the endothelium (Goto et al, 1999). But the details of this mechanism and the active components were not clear.…”
mentioning
confidence: 99%
“…Uncaria rhynchophylla (UR), an herbal plant, has been used in traditional oriental medicine ORIGINAL PAPER Uncaria rhynchophylla induces heme oxygenase-1 as a cytoprotective effect in RAW 264.7 macrophages over years to treat several vascular diseases, such as stroke, hypertension, and atherosclerosis. A recent study reported that UR has potent antihypertensive or vasodilator actions in animal models of hypertension 12,13 and neuroprotective effects against global cerebral ischemia in rats and antioxidant activity 14 , suggesting that it might be effective in the treatment of vascular dementia 15,16 . In the present study, we examined the induction of HO-1 expression by UR and its signaling pathway in RAW 264.7 macrophages. Our data indicate that enzyme induction is accompanied with Nrf2 nuclear translocation in RAW 264.7 cells.…”
mentioning
confidence: 99%